Relationship between NDVI and soil physicochemical properties in the Martabe gold mine reclamation area, Indonesia - Alfina, Rina; Iskandar, Iskandar; Suryaningtyas, Dyah Tjahyandari; Mulyanto, Budi; Nugraha, Candra; Asman, Auzia; Novfirman; Anwar, Syaiful; Pulungan, Yuni Hartinah (Brawijaya University, 2026)
Open-pit gold mining has greatly affected the ecological balance by altering soil properties and reducing natural vegetation cover. Reclamation efforts through soil and vegetation recovery are therefore essential to help rebuild the disturbed ecosystem. This study examined how the Normalized Difference Vegetation Index (NDVI) relates to soil physicochemical properties in the Martabe gold mine reclamation area, North Sumatra, Indonesia. Vegetation recovery at different reclamation ages was analyzed using multitemporal Landsat 8 images. Soil samples were taken from the same locations at depths of 0-15 cm and 15-30 cm to observe changes in soil characteristics. Data were analyzed using Principal Component Analysis (PCA) to identify the main factors linking vegetation and soil conditions. Key ecological indicators were determined through the Minimum Data Set (MDS) approach. The PCA results indicated that the primary components explained 90.7% of the variation in soil physical properties and 74.6% of the variation in chemical properties. Important indicators of the ecological recovery were NDVI, bulk density, porosity, aggregate stability, organic carbon, total nitrogen, cation exchange capacity (CEC), and base saturation. The rise in NDVI values coincided with improved soil conditions, showing a relationship between vegetation re-growth and soil quality improvement.